Assessment tool validation and technical skill improvement in the simulation of the Norwood operation using three-dimensional-printed heart models. (29th November 2020) - Hussein, Nabil; Honjo, Osami; Barron, David J; Haller, Christoph; Coles, John G; Van Arsdell, Glen; Lim, Andrew; Yoo, Shi-Joon
Abstract: OBJECTIVES: The hands-on surgical training course utilizes 3-dimensional (3D)-printed heart models to simulate complex congenital heart operations. This study aimed to validate a model and assessment tool in the simulation of 2 techniques of the Norwood operation and investigate whether technical performance improves following rehearsal with or without proctor presence. METHODS: Five 'experienced' and 5 'junior' surgeons performed 2 techniques of the Norwood operation on 3D-printed models of hypoplastic left heart syndrome. Performances were retrospectively assessed by 10 raters with varying experience in congenital heart surgery (CHS) (Medical Doctorate versus non-Medical Doctorate). Assessments were made with the procedure-specific Hands-On Surgical Training-CHS tool. Results were analysed for technical performance and rater consistency. Following validation, 30 surgeons (24 with proctor guidance and 6 with training videos and objective feedback only) simulated the Norwood operation twice. RESULTS: Performance scores were consistently higher for experienced surgeons and raters discriminated clearly between the experienced and junior surgeons ( P ≤ 0.001). The hands-on surgical training-CHS tool showed high inter-rater (0.86) and intra-rater (0.80) reliability among all raters. Scores for both experienced and junior surgeons were highly consistent across all raters, with no statistically significant difference ( P  = 0.50). All surgeons successfully performed the Norwood operation. Sixty attempts were scored in total. Eighty-seven percentage (26/30) of surgeons' scores (mean: attempt 1 = 92, attempt 2 = 104) and times [mean: attempt 1 = 1:22:00, attempt 2 = 1:08:00 (h:mm:ss)] improved between the 2 attempts by 9% and 15% respectively ( P ≤ 0.001). Total scores of all surgeons in the non-proctored subgroup (6) improved by 15% on average (mean: attempt 1 = 86, attempt 2 = 105, P  = 0.002). CONCLUSIONS: Procedure-specific assessment tools can be developed to evaluate technical performance for complex CHS simulation and be performed reliably by non-expert raters. Rehearsal both under supervision and independently leads to technical skill improvement further supporting its value in CHS training. Abstract : Congenital heart surgery (CHS) is a technically challenging speciality due to the wide variety and rarity of cases and the high risks associated with patients.